Reading and Writing The Qur’an to Improve The Faith andPiety Of Student At Muhammadiyah Elementary Schools: Pembiasaan Baca Tulis Al-qur’an Untuk Meningkatkan Keimanan Dan Ketaqwaan Siswa Di Sekolah Dasar Muhammadiyah - Dwi Silvi Atuszahroh; Risha Dwi Nur Laily; Andina Nurnida Hidayanti; Nur Efendi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Character education in elementary schools serves as a crucial foundation for student moral growth. Specific Background Muhammadiyah Elementary Schools implement structured Qur’anic reading and writing habituation to build Islamic character from an early age. Knowledge Gap Limited empirical research addresses how daily Qur’anic literacy routines simultaneously nurture student cognitive skills, faith, and piety. Aims This study investigates the contribution of Qur’anic reading and writing habituation to enhancing elementary student faith and piety. Results Findings show that systematic routines involving reading, writing hijaiyah letters, and memorizing short surahs significantly improve student worship discipline, religious confidence, and Islamic morals. Novelty The research reveals an integrated habituation model connecting motoric writing exercises with spiritual character formation in elementary education. Implications These insights offer a practical framework for primary schools to establish effective religious habituation strategies that strengthen foundational faith and daily piety. Key Findings Highlights Structured daily Qur’anic literacy routines foster early cognitive and spiritual development simultaneously. Step-by-step hijaiyah writing and memorization exercises enhance student worship discipline and confidence. Integrated religious habituation effectively builds long-term piety and Islamic moral character in students. Keywords: Qur’anic Literacy, Elementary School, Faith Development, Piety Habituation, Islamic Character